2017
DOI: 10.1002/dvdy.24481
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and hyperoxia differentially control proliferation of rat neural crest stem cells via distinct regulatory pathways of the HIF1α–CXCR4 and TP53–TPM1 proteins

Abstract: Our results show for the first time that extreme oxygen tensions directly control NCSC proliferation differentially via distinct regulatory pathways of proteins, with hypoxia via the HIF1α-CXCR4 pathway and hyperoxia via the TP53-TPM1 pathway. Developmental Dynamics 246:162-185, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 158 publications
(230 reference statements)
0
10
0
Order By: Relevance
“…We also identified that HIF-1α can be upregulated in TNBC cells after short-term hyperoxia exposure. There is a vast body of literature demonstrating that HIF-1α increases in hypoxia while in hyperoxic regimens usually decreases [17,18]. However, in skeletal muscle cells under high oxygen concentrations (42%), the amount of HSP90-HIF-1α complex is increased and suggests that HSP90 stabilizes cytoplasmic HIF-1α under high oxygen levels [39].…”
Section: Angiogenesis Is Enhanced By 6 H O 2 Exposure In Triple Negatmentioning
confidence: 99%
See 2 more Smart Citations
“…We also identified that HIF-1α can be upregulated in TNBC cells after short-term hyperoxia exposure. There is a vast body of literature demonstrating that HIF-1α increases in hypoxia while in hyperoxic regimens usually decreases [17,18]. However, in skeletal muscle cells under high oxygen concentrations (42%), the amount of HSP90-HIF-1α complex is increased and suggests that HSP90 stabilizes cytoplasmic HIF-1α under high oxygen levels [39].…”
Section: Angiogenesis Is Enhanced By 6 H O 2 Exposure In Triple Negatmentioning
confidence: 99%
“…EMT induces new cancer stem cell formation that may be responsible for cancer recurrence. However, very high levels of ROS induced by exposure to over 80% O 2 are deleterious and induce apoptosis [18]. This suggests that there is a narrow window in which certain degree of hyperoxia can promote cancer progression.We hypothesize that high concentration oxygen exposure, even of short duration, may have long term effects on cancer progression, mainly during the perioperative period when the above mentioned concurrent factors intervene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The expression in NC migrating cells of genes involved in NCC delamination, such as SNAIL2, SOX10 or C-X-C chemokine receptor type 4 (CXCR4), was higher under hypoxic conditions, stimulating the migration of NCC. Hypoxia seems to induce proliferation in rat neural crest stem cells [21]. Both phenomena were dependent on hypoxia inducible factor 1 alpha (HIF-1α), a transcription factor typically stabilised and activated under hypoxic conditions.…”
Section: Hypoxia and The Origin Of Neuroblastomamentioning
confidence: 99%
“…Hypoxia-mediated gene-expression regulation in neuroblastoma. HIF-1α, HIF-2α, SNAIL-2, SOX10, CXCR4, PDGF1-α, FZD-6, TRKAIII[21][22][23]25,26,31] …”
mentioning
confidence: 99%